THE RISE OF AI IN CONTENT MANAGEMENT: REIMAGINING INTELLIGENT WORKFLOWS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
As content management systems (CMS) become indispensable for managing digital experiences, AI integration promises to bring new levels of automation and intelligence to streamline workflows. This paper surveys how AI techniques like machine learning, natural language processing, computer vision, and knowledge graphs are transforming CMS capabilities across the content lifecycle. We analyze key use cases like automated metadata tagging, natural language generation, smart recommendations, predictive search, personalized experiences, and conversational interfaces. The benefits include enhanced content discoverability, accelerated creation, improved optimization, simplified governance, and amplified team productivity.However, adoption remains low due to challenges like opaque AI, poor workflow integration, unrealistic expectations, bias risks, and skills gaps. Strategic priorities include starting with focused pilots, evaluating multiple AI approaches, emphasizing transparent and fair AI models, and upskilling teams. Benefits are maximized through hybrid human-AI collaboration vs full automation. While AI integration is maturing, the outlook is cautiously optimistic. Leading CMS platforms are accelerating development of no-code AI tools. But mainstream adoption may take 2-5 years as skills and best practices evolve around transparent and ethical AI. Wise data practices, change management, and participatory design will be key.If implemented thoughtfully, AI can reimagine workflows by expanding human creativity, not replacing it. The future points to creative synergies between empowered users and AI assistants. But pragmatic pilots, continuous improvement, and participatory strategies are necessary to navigate the hype and deliver value. The promise warrants measured experimentation.